Modelling the performance of devices based on thin dielectric elastomer membranes. (October 2019) - Kumar Srivastava, Arpit; Basu, Sumit
Highlights: An explicit Finite Element code is developed within the framework of finite deformation hyper-viscoelastic material model to simulate the deformation of thin dielectric elastomer membranes subjected to an electrostatic potential applied across its faces. Characterising tests are performed on the commonly used dielectric elastomer material VHB4910 in order to determine its hyper-viscoelastic and electrical properties. The model is used to simulate the response of a simple cylindrical actuator configurations over a large number of cycles. The model predicts the response of the actuator under cyclic loading very well. The simulation scheme can also predict the mode of failure by initiation of wrinkles or electrical breakdown and help in determining the region of safe operation of the actuator configuration. Abstract: Actuators based on thin dielectric elastomer (DE) membranes with very low modulus, high dielectric permittivity and dielectric breakdown strength have recently been used in a number of diverse applications. In order to be technologically viable, the fidelity of their responses, especially in operations over large number of cycles, and failure mechanisms need to be understood and modelled. We present a simple, uncoupled, explicit scheme for simulating actuators based on DE membranes that depends on a characterisation of the material as a electro-visco-hyperelastic one. Experimental charactersiation of the uniaxial viscoelastic stress strain response, stretch dependent dielectric permittivity and breakdown strength of a commonly used DE material has been carried out. The simulation methodology has been verified against the performance of a circular membrane based actuator subjected to a cyclic potential. The simulations reproduced the experimental responses well and also allowed us to computationally map out the parameter space for safe operation of the actuator.